Commentary - McLaren, Anne (Cambridge quarterly of healthcare ethics, 1998)
In Lewis Carroll's Alice Through the Looking-Glass, Humpty Dumpty said: “When I use a word, it means just what I choose it to mean—neither more nor less.” One may not agree with this approach, but it may well be preferable to using a word: (a) with only a vague idea of its meaning, or (b) with many possible meanings.